Influence of Profitability, Leverage, Liquidity, & Firm Size from Tax Avoidance on Sharia General Banks (SGB) In Indonesia Year 2020-2024 - Ramadhan, Ikhsan; Mulyani, Sri; Rosida, Siti Ayu (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study was conducted to examine the Influence of Profitability, Leverage, Liquidity, & Firm Size from Tax Avoidance on Sharia General Banks (SGB) In Indonesia Year 2020-2024. The methodology used in this study is a quantitative method. The data used is secondary data obtained from the annual financial statements of Sharia General Banks registered with the Otoritas Jasa Keuangan (OJK) for the period 2020-2024 using the purposive sampling method. Data analysis was carried out using SPSS 26. The test results show that profitability, leverage, liquidity, and firm size have no partial effect on tax avoidance. Simultaneously, the variables of profitability, leverage, liquidity, and firm size have no effect on tax avoidance.